WS2 nanosheets functionalized by biomimetic lipids with enhanced dispersibility for photothermal and chemo combination therapy. Issue 11 (26th February 2020) - Xie, Meng; Yang, Mei; Sun, Xuan; Yang, Na; Deng, Tongtong; Li, Yeping; Shen, Haijun
Abstract : A WS2 -lipid nanocarrier with enhanced stability and intratumoral accumulation was synthesized for photothermal-chemo combination therapy Abstract : Multi-component combination therapy of cancer is currently a hot spot in the field of cancer treatment research. In this study, a WS2 nanosheet was selected as the substrate material and modified with a cell-like membrane biomimetic liposome (WS2 -lipid). The lipid-modified WS2 nanomaterials were successfully prepared with good stability and biocompatibility. Its good photothermal characteristics and high drug loading amount were utilized to achieve a comprehensive chemo and photothermal therapeutic effect. The results showed that the lipid coating strongly enhanced the stability of the WS2 nanosheets before and after DOX loading and the WS2 -lipid had a good photothermal performance and drug loading amount. According to the cellular results, WS2 -lipid was able to be taken up by MCF-7 cells. Both photothermo-therapy and chemotherapy had a concentration dependent cytotoxicity on MCF-7 cells, and the combined application of both methods had an improved cytotoxicity. In addition, in vivo photothermal experiments indicated that lipid modification could promote intratumoral accumulation of the material. Thus, WS2 -lipid can be used as a good nano-platform for phototherapy and chemotherapy combination therapy and has good application prospects in cancer therapy.